Consommation du miel en Algérie - DAGHEB, Khedidja (My University, 2020)
This survey on the consumption of honey in Algeria tries to draw a portrait, in the current context of the beekeeping sector, of the perception of the Algerian consumer of honey, his expectations, preferences, uses, and knowledge of their components. We prepared a questionnaire, and we tried to see the population which consumes honey. The questionnaire was given to 115 respondents. The results show that the Algerian consumes between one and two 500 g jars per year, the Algerian consumer uses honey as a throat remedy, his preferences are for liquid, local honey in glass jars.
Keywords: honey; survey; consumption; Algeria